Robust Expression of Functional NMDA Receptors in Human Induced Pluripotent Stem Cell-Derived Neuronal Cultures Using an Accelerated Protocol - Ruden, Jacob B.; Dixit, Mrinalini; Zepeda, José C.; Grueter, Brad A.; Dugan, Laura L. (Frontiers in Molecular Neuroscience, 2021)
N-methyl-D-aspartate (NMDA) receptors are critical for higher-order nervous system function, but in previously published protocols to convert human induced pluripotent stem cells (iPSCs) to mature neurons, functional NMDA receptors (NMDARs) are often either not reported or take an extended time to develop. Here, we describe a protocol to convert human iPSC-derived neural progenitor cells to mature neurons in only 37 days. We demonstrate that the mature neurons express functional NMDARs exhibiting ligand-activated calcium flux, and we document the presence of NMDAR-mediated electrically evoked postsynaptic current. In addition to being more rapid than previous procedures, our protocol is straightforward, does not produce organoids which are difficult to image, and does not involve co-culture with rodent astrocytes. This could enhance our ability to study primate/human-specific aspects of NMDAR function and signaling in health and disease.